2009
DOI: 10.1152/ajpendo.00315.2009
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-sensing receptor (CaSR) defends against hypercalcemia independently of its regulation of parathyroid hormone secretion

Abstract: Kantham L, Quinn SJ, Egbuna OI, Baxi K, Butters R, Pang JL, Pollak MR, Goltzman D, Brown EM. The calcium-sensing receptor (CaSR) defends against hypercalcemia independently of its regulation of parathyroid hormone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 50 publications
6
105
2
3
Order By: Relevance
“…Nevertheless, PTH seemed to set a floor level defending against hypocalcemia, mindful that KO of claudin-14 could not correct the hypocalcemia induced by cinacalcet. This phenomenon has also been observed in the work by Kantham et al, 40 which showed that the presence of CaSR in the setting of PTH KO could not rescue the CaSR/PTH double KO from hypocalcemia.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, PTH seemed to set a floor level defending against hypocalcemia, mindful that KO of claudin-14 could not correct the hypocalcemia induced by cinacalcet. This phenomenon has also been observed in the work by Kantham et al, 40 which showed that the presence of CaSR in the setting of PTH KO could not rescue the CaSR/PTH double KO from hypocalcemia.…”
Section: Discussionsupporting
confidence: 71%
“…An important finding from these mice was the clear demonstration that suppression of PTH was not required for robust defense against various hypercalcemic challenges. 40 40 A direct support for the renal role of CaSR in defending hypercalcemia was provided by Toka et al 41 With a kidney-specific CaSR KO mouse model, Toka et al 41 have elegantly shown that the KO mice excrete significantly less Ca ++ in face of hypercalcemia, although their PTH secretion was intact. Loupy et al 14 have studied the renal role of CaSR in cases of hypercalcemia induced by the calcilytic compound NPS2143.…”
Section: Discussionmentioning
confidence: 99%
“…Data from these models suggest that the extraparathyroid CaSR may limit the variability of blood and urine Ca (8). Moreover, studies in mice have shown that the CaSR in kidney and/or C cells plays an important homeostatic role in the defense against hypercalcemia induced by oral Ca overload or by PTH or calcitriol administration (9,10). However, these experiments did not aim at providing evidence that extraparathyroid CaSR plays a significant role as a direct determinant of blood Ca concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it appears that PTH is necessary for the maintenance of normal serum calcium concentrations when facing a hypocalcaemic challenge, but that PTH-independent mechanisms, such as CaSR-stimulated CT secretion and increased renal Ca 2C excretion, are involved in maintaining normal serum calcium concentrations in response to hypercalcaemic challenges (Kantham et al 2009).…”
Section: Pthmentioning
confidence: 99%